Lysosomal Storage Disorders and Malignancy - Gregory M. Pastores; Derralynn A. Hughes (Diseases, 2017)
Lysosomal storage disorders (LSDs) are infrequent to rare conditions caused by mutations that lead to a disruption in the usual sequential degradation of macromolecules or their transit within the cell. Gaucher disease (GD), a lipidosis, is among the most common LSD, with an estimated incidence of 1 in 40,000 among the Caucasian, non-Jewish population. Studies have indicated an increased frequency of polyclonal and monoclonal gammopathy among patients with GD. It has been shown that two major sphingolipids that accumulate in GD, namely, β-glucosylceramide 22:0 (βGL1-22) and glucosylsphingosine (LGL1), can be recognized by a distinct subset of CD1d-restricted human and murine type II natural killer T (NKT) cells. Investigations undertaken in an affected mouse model revealed βGL1-22- and LGL1-specific NKT cells were present and constitutively promoted the expression of a T-follicular helper (TFH) phenotype; injection of these lipids led to downstream induction of germinal center B cells, hypergammaglobulinemia, and the production of antilipid antibodies. Subsequent studies have found clonal immunoglobulin in 33% of sporadic human monoclonal gammopathies is also specific for the lysolipids LGL1 and lysophosphatidylcholine (LPC). Furthermore, substrate reduction ameliorated GD-associated gammopathy in mice. It had been hypothesized that chronic antigenic stimulation by the abnormal lipid storage and associated immune dysregulation may be the underlying mechanism for the increased incidence of monoclonal and polyclonal gammopathies, as well as an increased incidence of multiple myeloma in patients with GD. Current observations support this proposition and illustrate the value of investigations into rare diseases, which as ‘experiments of nature’ may provide insights into conditions found in the general population that continue to remain incompletely understood.